Democratic Head Nurse Leadership and Interprofessional Collaboration in Hospital Settings: A Cross-Sectional Study - Nur Mukarromah; Berliana Hanifah Alisya; Abdul Aziz Alimul Hidayat; Puji Rahayu; Diah Priyantini (Universitas Airlangga, 2026)
Introduction: Effective nurse–doctor collaboration is fundamental to delivering high-quality hospital care. However, interprofessional collaboration often remains suboptimal due to hierarchical dynamics and limited managerial competence among nurse leaders. This study examined the influence of head nurses’ leadership style, particularly democratic leadership, on nurse–doctor collaboration in hospital settings. Methods: a cross-sectional correlational study was conducted at a regional general hospital in Indonesia, with data collected in April 2023. A total of 49 respondents were recruited using purposive sampling. Leadership style was assessed using the Multifactor Leadership Questionnaire (MLQ–5X Rater Form, 45 items), while nurse–doctor collaboration was measured with the Jefferson Scale of Attitudes toward Physician–Nurse Collaboration (JSAPNC, 15 items). Content validity was established through expert judgment (CVI = 0.87), and reliability testing demonstrated good internal consistency (Cronbach’s α = 0.82 for MLQ; α = 0.85 for JSAPNC). Data were analyzed using the Chi-square test with a significance level of p < 0.05. Results: In major (69.4%) respondents perceived their head nurse’s leadership style as democratic. Additionally, 61.2% reported good nurse–doctor collaboration. Statistical analysis revealed a significant association between democratic leadership style and nurse–doctor collaboration (p < 0.001). Conclusions: Democratic leadership among head nurses is significantly associated with stronger nurse–doctor collaboration. Enhancing democratic leadership competencies may promote more effective interprofessional teamwork and contribute to improved quality of care in hospital settings.